A note on number fields having reciprocal integer generators. Issue 3 (28th April 2017) - Zaïmi, Toufik
Abstract: We prove that a totally complex algebraic number field K, having a conjugate which is not closed under complex conjugation, can be generated by a reciprocal integer, when the Galois group of its normal closure is contained in the hyperoctahedral group B deg( K )/2 .